2007
DOI: 10.1002/evan.20142
|View full text |Cite
|
Sign up to set email alerts
|

Gorilla society: What we know and don't know

Abstract: Science is fairly certain that the gorilla lineage separated from the remainder of the hominoid clade about eight million years ago,2, 4 and that the chimpanzee lineage and hominin clade did so about a million years after that.1, 2 However, just this year, 2007, it was discovered that although the human head louse separated from the congeneric chimpanzee body louse (Pediculus) around the same time as the chimpanzee and hominin lineages split,3 the human pubic louse apparently split from its sister species, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 81 publications
1
41
0
Order By: Relevance
“…Further, availability of subordinate males as coalition partners does not occur until natal males mature (Robbins, ; Sicotte, ; Stoinski et al, ; Watts, ). Thus, dispersing males face a long period where they alone must defend their newly‐formed groups in interunit encounters, during which rates of aggression are higher than within groups (Robbins, ) and may lead to injury and infanticide (also see Fossey, ; Harcourt & Stewart, ; Rosenbaum, Vecellio, & Stoinski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, availability of subordinate males as coalition partners does not occur until natal males mature (Robbins, ; Sicotte, ; Stoinski et al, ; Watts, ). Thus, dispersing males face a long period where they alone must defend their newly‐formed groups in interunit encounters, during which rates of aggression are higher than within groups (Robbins, ) and may lead to injury and infanticide (also see Fossey, ; Harcourt & Stewart, ; Rosenbaum, Vecellio, & Stoinski, ).…”
Section: Discussionmentioning
confidence: 99%
“…If male tenure length is shorter than a male's age to mature, age-graded groups are unlikely to develop. This scenario could provide an alternative explanation for the lack of multimale (kin) groups in western gorillas compared with mountain gorillas [see alternative explanation in Harcourt & Stewart, 2007].…”
Section: Implications For Life-history Theory Social Organization Anmentioning
confidence: 99%
“…This is most marked in chimpanzees and bonobos, which show multimale-multifemale mating structures in which females mate with most of the unrelated males in their communities. In gorillas, which show primarily polygynous mating structures in which a single dominant male fathers most of the offspring, females commonly disperse when they mature, whereas males either leave or remain until they have an opportunity to attain dominant status in the group (Harcourt and Stewart 2007). These observations have suggested that male philopatry may be an ancestral feature of African apes and humans (Wrangham 1987).…”
mentioning
confidence: 99%